Influence of surface pre-treatment on the electronic levels in silicon MaWCE nanowires. (22nd April 2015) - Venturi, Giulia; Castaldini, Antonio; Schleusener, Alexander; Sivakov, Vladimir; Cavallini, Anna
Abstract: Deep level transient spectroscopy (DLTS) was performed on n-doped silicon nanowires grown by metal-assisted wet chemical etching (MaWCE) with gold as the catalyst in order to investigate the energetic scheme inside the bandgap. To observe the possible dependence of the level scheme on the processing temperature, DLTS measurements were performed on the nanowires grown on a non-treated Au/Si surface and on a thermally pre-treated Au/Si surface. A noticeable modification of the configuration of the energy levels was observed, induced by the annealing process. Based on our results on these MaWCE nanowires and on literature data about deep levels in bulk silicon, some hypotheses were advanced regarding the identification of the defects responsible of the energy levels revealed.